Long-run sectoral development time series evidence for the German economy - Andreas Dietrich; Jens J. Krüger (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In economic development, long-run structural change among the three main sectors of an economy follows a typical pattern with the primary sector (agriculture, mining) first dominating, followed by the secondary sector (manufacturing) and finally by the tertiary sector (services) in terms of employment and value added. We reconsider the verbal theoretical work of Fourastié and build a simple model encompassing its main features, most notably the macroeconomic influences on the sectoral development. Estimation and analysis with German data for the period 1850-2001 show that this model is quite capable to replicate the empirical facts.
Keywords: L16; O14; O41; 330; structural change; industrialization; tertiarization; Drei-Sektoren-Hypothese; Strukturwandel; Schätzung; Deutschland